REMNANTS OF AN UNWANTED PAST: ESTATE INSTITUTION OF PRESERVATION STUDIES FOR THE PAULISTA NETWORK OF PROPHYLAXIS AND TREATMENT OF HANSEN’S DISEASE - Caporrino, Amanda W.; Ungaretti, Adda A. P. (Revista CPC, 2016)
This article presents the results of the studies for the State heritage listing of the remnants of the Paulista network of prophylaxis and treatment of Hansen’s disease, formerly known as leprosy. This network was created based on a hospital model of isolation known as leper colony, adopted in Brazil in the early 1920s when the compulsory hospitalization of people with Hansen’s disease was determined by law. In the 1930s, its implementation was completed with the construction of five leper colonies: Santo Ângelo (Mogi das Cruzes), Padre Bento (Guarulhos), Pirapitingui (Itu), Cocais (Casa Branca) and Aimorés (Bauru). The prophylactic and treatment structure was also composed of clinics called dispensaries and preventoriums, orphanages for healthy children of leprosy patients hospitalized. In face of the challenges and advances proposed by the research, this article also aims to contribute to discussions about the recognition as cultural heritage of the remnants connected to relegated pasts and difficult memories.